Functional outcome prediction of ischemic stroke patients with atrial fibrillation accepting post-acute care training - Liu, Sen-Yung; Hsu, Ying-Lin; Tu, Yi-Chun; Lin, Ching-Hsiung; Wang, Shih-Chun; Lee, Ya-Wen; Shih, Yin-Tzer; Chou, Ming-Chih; Lin, Chih-Ming (Frontiers in Neurology, 2022)
Ischemic stroke poses a major threat to human health and represents the third leading cause of death worldwide. Post-acute care has been reported to be beneficial post index stroke event. However, there is still a lacking knowledge as to outcome of stroke events derived from cardiac origin. The focus of current project is to investigate the effectiveness of PAC to this subgroup as well as finding out baseline key pointers that are capable of early predict patients’ physical recovery. 142 ischemic stroke patients with underling cardiac arrhythmia were recruited. The patients’ basic demographics were accurately documented. The pre and post admission NIHSS, Barthel index, and mRS score were also recorded. All statistical analyses were performed using R for Windows. A multivariate logistic analysis was designed and was applied to assess the significance of risk factors. The utilization of the receiver operating characteristic and the Youden Index was to find the important cut-off point information, and the area under the curve is calculated to provide the accuracy. The average age of the patients enrolled is around 66-year-old and consist of 88 males and 54 females. The most common underlying diseases were: mixed hyperlipidemia (60.56%), essential hypertension (80.99%) and diabetes mellitus (34.51%).While conducting the EQ-5D assessment, anxiety / depression stood out as the most prominent domain, affecting 44 patients (30.99 %). Multivariate logistic analysis of both NIHSS and Barthel Index shows improvement with a contralateral plaque index statistical significance, whereas NIHSS shows a relevant significance in anxiety/ depression and Barthel Index of usual activity in the data analysis. Youden index analysis shows cutoff point both in NIHSS and Barthel Index of contralateral plaque index of 4.5, this being the significant value for this group of patients. The outcome assessments seem to correlate well with NIHSS and Barthel Index scores, rather than mRS. The anxiety /depression and usual activities domains of the EQ-5D results after intense training are associated with and have a great impact after the patients undertaking the PAC rehabilitative strategy. The carotid duplex produced variables and plaque index might also play a significant role in determining the patients’ functional outcome.